Determining the Effect of Emotional Intelligence on Self-Leadership - Ülkuhan Bike Esen; Sinan Bulut (Journal of Business and Management Review, 2022)
The aim of the study is to determine the relationship between emotional intelligence and self-leadership levels of students studying at the Faculty of Health Sciences. The students of the Faculty of Health Sciences have been selected in the study, because the students of this faculty will be a part of the health system when they graduated. A successful healthcare system requires individuals who can work independently, control themselves, empathize with others, use initiative, know their responsibilities and make effective decisions. These features are only seen in individuals with high emotional intelligence and self-leadership levels. For this purpose, first of all, the concepts of emotional intelligence and self-leadership have been discussed in the study, and then the effect of emotional intelligence on self-leadership and the interactions between the sub-dimensions of these concepts have been analyzed by structural equation modeling. As a result of the research, it has revealed that emotional intelligence has a positive and significant effect on self-leadership.